Quality of life in women with type 2 diabetes mellitus and obesity assessed by the SF-12v2 questionnaire - Khodjaeva, Nodira; Abdinazarova , Maftuna; Khodjayeva , Feruza (Uzbekistan Open Conference, 2026)
Type 2 diabetes mellitus is a chronic metabolic disease frequently associated with obesity, impaired glycemic control, dyslipidemia, and a substantial reduction in health-related quality of life. The aim of this study was to assess the quality of life in women with type 2 diabetes mellitus and obesity using the SF-12v2 questionnaire and to compare physical and mental health components with those of women with type 2 diabetes mellitus without obesity. A comparative clinical study included 120 women with type 2 diabetes mellitus, divided into a main group consisting of patients with obesity (n=100) and a control group without obesity (n=20). Health-related quality of life was evaluated using the SF-12v2 questionnaire with calculation of the Physical Component Summary (PCS) and Mental Component Summary (MCS) scores based on the standardized norm-based scoring algorithm. In addition, body mass index, glycated hemoglobin (HbA1c), total cholesterol, and triglyceride levels were assessed. The mean body mass index was significantly higher in the main group compared with the control group: 31.70 +/- 4.37 kg/m² versus 22.85 +/- 0.60 kg/m². Women with type 2 diabetes mellitus and obesity demonstrated markedly lower quality-of-life scores: PCS was 39.91 +/- 5.32 compared with 51.09 +/- 3.32 in the control group, and MCS was 37.59 +/- 5.95 compared with 50.33 +/- 1.43, respectively. Both differences were statistically significant (p
Keywords: Type 2 diabetes mellitus; obesity; quality of life; SF-12v2; Physical Component Summary; Mental Component Summary; metabolic profile